Pelatihan Pembuatan Media Pembelajaran Yang Menarik dan Interaktif Berbasis AI Untuk Meningkatkan Kompetensi Guru Di SD Negeri Jelapat II.I - Alim, Agus Alim Muin; silvia ratna; Erfan Karyadiputra; Agus Setiawan; Sefto Pratama; Fauzi Yusa Rahman (Jurnal Inovasi Pengabdian Masyarakat, 2025)
The availability of professional human resources, especially teachers, is the primary capital to improve the quality of human resources, particularly in the field of education. Therefore, efforts are needed to enhance the understanding and abilities of educators in keeping up with technological advancements and utilizing these technological facilities in teaching and learning activities in schools. At SD Negeri Jelapat II.I, there is a limitation in utilizing technological media for learning, which is integrated with AI as part of the learning process. Many teachers still use conventional methods that are not engaging for students, which can affect the low motivation and learning outcomes of students. Presentation methods such as socialization activities to enhance knowledge, training and mentoring methods, as well as self-practice methods can improve participants' skills in using learning media from Canva AI, Quiziiz, Wordwall, and applications like ChatGpt, Meta, and Gemini to enhance the competencies of teachers at SD Negeri Jelapat II.I. after the implementation of a series of training activities for the development of skills and expertise for teachers at SD Negeri Jelapat II.I. there has been an increase in the abilities and skills of the teachers by an average of 59,5% in terms of creating AI-based web media.